Peran Penting Regulasi Sertifikasi Halal dalam Kepatuhan UMKM pada Gethuk Frozen Mama Wina di Desa Wonosari - Jovita Nana Anggreini; Maulana Ihsyan Azwar; Fiki Mursida; Aang Anshari (Lembaga Pengembangan Kinerja Dosen, 2024)
Halal certification plays a very important role for Micro, Small and Medium Enterprises (MSMEs), especially in an increasingly competitive market. For MSMEs, halal certification is not just a label but also a strategic tool that can increase competitiveness and consumer confidence. This study uses a qualitative method to understand the important role of halal certification regulations in MSME compliance at “Gethuk Frozen Mama Wina” in Wonosari Village. The qualitative method was chosen because it allows researchers to explore and gain an in-depth understanding of the subjective experiences and views of various related parties. Primary data was collected through in-depth interviews with Ms. Wina, the owner of Gethuk Frozen, and some of her regular customers. The results of this study highlight the important role of halal certification regulations in MSME compliance, especially at Gethuk Frozen Mama Wina in Wonosari Village. The results of interviews with Ms. Wina and consumers show that halal certification has a significant impact on various aspects of MSME operations and marketing.